Association of IL-10 gene polymorphisms and susceptibility to Juvenile Idiopathic Arthritis in Egyptian children and adolescents: a case-control study. Issue 1 (January 2017) - Fathy, Manar; Elsaadany, Hosam; Ali, Yasser; Farghaly, Mohsen; Hamed, Mohammed; Ibrahim, Hany; Noah, Maha; Allah, Mayy; Elashkar, Shaimaa; Abdelsalam, Nasser; Abdelrahman, Hind; Ahmed, Ahmed; et al.
Abstract Background Juvenile Idiopathic Arthritis (JIA) is the most common chronic arthritis in children worldwide. Among anti-inflammatory cytokines, interleukin-10 (IL-10) is a key immunosuppressive cytokine involved in the pathogenesis of JIA. To date, only a few studies concerned the association of interleukin-10 gene polymorphisms with JIA. In this study, we aimed to investigate 3 cytokine single-nucleotide polymorphisms situated at positions -1082(G/A), −819(C/T), and −592(C/A) in the promoter region of the IL-10 gene to determine whether this polymorphism could be a marker of susceptibility to JIA in Egyptian children and adolescents. We also measured the serum level of IL-10 to assess its relation to such polymorphism. Methods This was a case-control study included 100 patients diagnosed with JIA, and matched with age, gender, ethnicity 100 healthy control subjects. Interleukin-10 −1082(G/A), −819(C/T), and −592(C/A) polymorphisms were genotyped by amplification refractory mutation system- polymerase chain reaction (ARMS)-PCR methodology, while the serum IL10 levels were measured byELISA method. Results Compared to the controls subjects, the frequency of IL-10- AA genotype and A allele at the –1082 position were overrepresented in patients with JIA (OR = 2.7; 95% CI: 1.1–6.4 for the AA genotype;P <0.05 and OR: 1.5; 95% CI: 1.03–2.3 for the A allele;P <0.05 respectively). On the other hand, no significant differences were found between the 2 groups in the genotype or allele frequencies for the –819 and –592 positions. Of note, we found a significant positive association between the IL-10 (-1082) AA genotype and susceptibility to polyarticular JIA (OR: 4.3; 95% CI: 1.5–12.7;P <0.01). We observed that patients with the IL-10 (-1082) AA genotype had significantly lower serum IL-10 levels (2.3 ± 0.9 pg/ml ) compared to those with AG genotype (7.6 ± 1.5 pg/ml ) and GG genotype (9.5 ± 1.2 pg/ml );P  < 0.01, respectively. Conclusion We demonstrate for the first time, to the best of our knowledge, that the presence of an A allele or AA gene variant at the –1082 position of the promoter region of the interleukin-10 gene may constitute risk factors for developing JIA in Egyptian children and adolescents. Moreover, we observed a significant positive association between the IL10 –1082 AA gene variant and susceptibility to polyarticular JIA.